School Management from the Perspective of Social Transformations at Work - Mauricio Bueno da Rosa; Eliane Griep Gomes Bitencourt; Muhammad Ridwan (Budapest International Research and Critics University, 2021)
In this article we intend to address the context of the school routine that is governed by rules developed by the sectors responsible for school management. In the bureaucratization of school work we see the same meaning and dimensions as the bureaucratization of other sectors of production. As the training of the workforce was transferred to the school, this institution incorporated in its organization and functioning new elements and fundamental characteristics to achieve a good performance as a socializing agency for the worker. On the other hand, the figure of the autonomous teacher, of the humanist, encyclopedist type, has also disappeared. Whether in public education or in the private network, the vast majority of teachers are in the condition of salaried workers. In this way, the process of proletarianization of teaching workers is characterized, characterized by their working conditions. The division of school work, as it developed based on the same principles as the so-called management theories, reinforces the reproduction of capitalist logic in school pedagogical practice because new practices and relationships are crystallized in this practice.